Route Optimisation For Mobile Ipv6 - Yahaya, Coulibaly (2002)
In the future it is expected that the number of terminals with wire less access to network re source swill be more wide spread, and it i s therefore necessary to integrate mobility support into future generation networks so that users can be on line, even while in motion. The increasing use of Internet suggests that the Internet technology can be the best candidate for effective realization of future generation mobile systems. Mobile IP can offer the possibility to use the mobile Internet in other ways than it is used in the standard wire d environment ,Because of this , mobility in IPv6( MlPv6) is designed to be scalable , stable , efficient and secure. This thesis focuses on an important aspect of mobility, which is route optimisation. We investigate the existing route optimisation techniques, especially base MIPv 6 route optimisation and propose an efficient route optimisation . Our proposed solution , Mobile node Address Multicasting technique ( MAM) is based on multicasting techniques different from base MIPv 6 route optimisation , which is based on bin ding update technique.